Environmental assessment of vegetable crops towards the water-energy-food nexus: A combination of precision agriculture and life cycle assessment. (July 2022) - Del Borghi, Adriana; Tacchino, Valeria; Moreschi, Luca; Matarazzo, Agata; Gallo, Michela; Arellano Vazquez, Diego
Graphical abstract: Highlights: Precision agriculture and life cycle approach are combined to assess vegetable crops. A cradle to grave analysis is performed to highlight hotspots of agricultural phase. The water-energy-food nexus of bean, pea, sweet corn and tomato is analysed. Optimal combination of ideotypes and crop management are evaluated. Abstract: The increase in world population and the resulting demand for food, water and energy are exerting increasing pressure on soil, water resources and ecosystems. Identification of tools to minimise the related environmental impacts within the food–energy–water nexus is, therefore, crucial. The purpose of the study is to carry out an analysis of the agri-food sector in order to improve the energy-environmental performance of four vegetable crops (beans, peas, sweet corn, tomato) through a combination of precision agriculture (PA) and life cycle assessment (LCA). Thus, PA strategies were identified and a full LCA was performed on actual and future scenarios for all crops in order to evaluate the benefits of a potential combination of these two tools. In the case study analysed, a life cycle approach was able to target water consumption as a key parameter for the reduced water availability of future climate scenarios and to set a multi-objective function combining also such environmental aspects to the original goal of yield maximisation. As a result, the combination of PA with the LCA perspective potentially allowed the path for an optimal trade-off of all the parameters involved and an overall reduction of the expected environmental impacts in future climate scenarios.